(untitled) - Booth, Alison (New York, 2006)
The Norton Introduction to Literature, Portable Edition, offers a balanced selection of classic and contemporary stories, poems, and plays in a brief and affordable format.
Keywords: Literature,Văn học; Collections,Bộ sưu tập